1983
DOI: 10.1104/pp.72.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Echinochloa crus-galli (Barnyard Grass) Seeds under Anaerobic Conditions

Abstract: (18)(19)(20). This paper presents information on the respiration and response to respiratory inhibitors of anaerobically grown Echinochloa seedlings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…Reduction of an alternate electron acceptor, such as nitrate (6) or organic acids (5,8), could permit electron transport in the absence of 02. In support of this hypothesis, we have found that nitrate reserves are depleted in oryzicola seeds during germination (13). Once germinated, the ability to rapidly shift from an anaerobic mode to an aerobic one may be an important metabolic feature during early establishment of this flood tolerant species.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Reduction of an alternate electron acceptor, such as nitrate (6) or organic acids (5,8), could permit electron transport in the absence of 02. In support of this hypothesis, we have found that nitrate reserves are depleted in oryzicola seeds during germination (13). Once germinated, the ability to rapidly shift from an anaerobic mode to an aerobic one may be an important metabolic feature during early establishment of this flood tolerant species.…”
supporting
confidence: 64%
“…In previous studies, we noticed that, unlike rice, germination of oryzicola is inhibited by cyanide and azide (13). In addition, tricarboxylic acid cycle intermediates are produced and acetate is readily metabolized under anaerobic conditions (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vol. 101, 19931983b, glycolysis (Rumpho and Kennedy, 1983a;Kennedy et al, 1987b), the oxidative pentose phosphate pathway (Kennedy et al, 1983;Rumpho and Kennedy, 1983a), lipid metabolism (VanderZee and Kennedy, 1982;Knowles and Kennedy, 1984;Everard and Kennedy, 1985), and mitochondrial activity (Kennedy et al, 1987a;Fox and Kennedy, 1991) operate under anaerobic conditions. Recently, we (Fox and Kennedy, 1991) reported that a complete TCA cycle was present in E. phyllopogon under anoxia and that most TCA cycle enzymes in nitrogen-grown seedlings exhibited in vitro activities comparable to those grown in air.…”
mentioning
confidence: 99%
“…Echinochloa crus-galli (L.) P.Beauv. is a grass weed that can germinate and grow for extended periods of time in an anaerobic environment (Kennedy et al 1983) which is ecologically similar to rice. Being a highly competitive weed with rice, it can reduce rice yield up to 100% (Nyarko & Datta 1991).…”
Section: Introductionmentioning
confidence: 99%